On Accumulation of the Budget Deficit: Spirit of MMT Through Mathematical Analysis - Tanaka, Yasuhito (Issues in Economics and Business, 2022)
It is said that public finance must be balanced at least in the long run. According to the so-called MMT (Modern Money Theory or Modern Monetary Theory) approach, however, this is not true. It is often pointed out that MMT lacks the mathematical analysis used in ordinary economic discussions. The purpose of this paper is to present a brief theoretical and mathematical basis to the backbone of the MMT argument, while maintaining the basics of the neoclassical microeconomic framework, such as maximizing consumer utility through utility functions and budget constraints, and equilibrium between demand and supply of goods under perfect competition with constant returns to scale technology. Using a simple overlapping generations (OLG) model that includes economic growth due to technological progress, we present the following results. The budget deficit equals the increase in people's savings, and the accumulated budget deficit equals people's savings. The budget deficit is a cause and the savings is a consequence, not the other way around. Deficits are created by the government, which determines income, which determines savings. Deficits create savings, not savings finance deficits. Reducing the budget deficit will reduce savings, income, and consumption.